Interactive ship cabin layout optimization. (15th February 2023) - Wang, Zhan; Yang, Xiao-qian; Zheng, Yu-hao; Chen, Wei-Chao; Lv, Pei; Zhou, Bing; Xu, Ming-liang
Abstract: Traditionally, the ship cabin layout is designed by experts with the help of CAD, GAD, etc. The layout is usually drawn and designed repeatedly, which is not only labor-intensive but also time-consuming. Although a layout is well-thought-out, potential design issues may still exist in practice. In recent years, some intelligent ship layout design algorithms are proposed. However, the capability of involving humans in the loop has been seriously overlooked in current studies, which are mostly end-to-end approaches. To resolve these challenges, we propose a novel interactive ship cabin layout optimization approach based on integer programming (IP), which is capable to generate diverse layouts and interact with designers for further refinement. Gurobi, an integer programming solver, is adopted to find out the optimal value under the layout constraints in our approach. Moreover, crowd simulation is used to evaluate the layout quality from the perspective of coziness and mobility. The results indicate the proposed method can effectively design and optimize the ship cabin layout in an interactive manner. Highlights: This paper proposes an interactive optimization approach for the ship cabin layout design. Our method assists designers to complete repetitive and complex operations automatically. The mobility and coziness metrics of crowd simulation are introduced to evaluate the ship cabin layouts. Designers can define the passages in arbitrary shapes, breaking the limitation of predefined passage patterns.